Meningkatkan Prestasi Belajar Pendidikan Agama Islam Dengan Penerapan Metode Pembelajaran Kooperatif Model Group Investigations Pada Siswa Kelas IX B SMPN 3 Dolopo Tahun Pelajaran 2021/2022 - Nurul Hidayati (Jurnal Multidisiplin Madani, 2022)
Islamic Religious Education is a study material that has an abstract object and is built through a deductive reasoning process, namely the truth of a concept is obtained as a logical result of the previously accepted truth, so that the interrelationships between concepts in Islamic Religious Education are very strong and clear. The aims of this research are: (a) Want to know the increase in student achievement after the implementation of the Group Investigations model of cooperative learning method. (b) Want to know the impact of students' learning motivation after applying the Group Investigations model of cooperative learning. This research uses three cycles of action research. Each cycle consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is class IX B students of SMPN 3 Dolopo. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (62.50%), cycle II (78.12%), cycle III (93.75%). The conclusion of this study is that the cooperative method of the Group Investigations model can have a positive impact on the learning motivation of class IX B students of SMPN 3 Dolopo and this learning model can be used as an alternative to learning Islamic Religious Education.